ANALISIS PENGARUH RASIO AKTIVITAS, RASIO LIKUIDITAS, UKURAN PERUSAHAAN DAN RASIO PROFITABILITAS TERHADAP LEVERAGE PADA PERUSAHAAN PANGAN YANG TERDAFTAR DI BEI TAHUN 2014-2019 - Bismoko Dwi Wijayanto (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
AbstractThis study aimed to examines the effect of activity ratio, liquidity ratio, firm size and profitability ratio to leverage in consumer goods companies listed in BEI (Bursa Efek Indonesia) from period 2014-2019. Based on purposive sampling method, total sample of this research is 102. The data collection method used are observation, interview, and documentation.Hypotesis testing used is multiple regression analysis with SPSS. The result show that both liquidity ratio and firm size have significant effect to leverage. This is indicate that the firms using their current asset efficiently and firm size have bargaining power to influence their investor while activity ratio and profitability have not significant effect to leverage.